2022
DOI: 10.3390/s22124350
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experiment Analysis of Temperature Field of Magnetic Suspension Support Based on FBG

Abstract: Temperature rise is an important factor limiting the development of magnetic suspension support technology. Traditional temperature sensors such as thermocouples are complicated and vulnerable to electromagnetic interference due to their point contact temperature measurement methods. In this paper, the equivalent model of magnetic suspension support is established, and the temperature field is simulated and analyzed by magnetic thermal coupling calculation in ANSYS software. Then, a quasi-distributed temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The initial part of the numerical simulation is to engineer the geometric structure of the sensor, after structural engineering is carried out, work continues to define the constituent materials of each designed geometric structure, such as defining the RI of air holes, defining RI of SiO2 material using (6), and the last is to define plasmonic material (gold). After the design and material have been defined in COMSOL multiphysics, a mode analysis of the design is performed with the ultimate gold of obtaining the imaginary effective RI for each wavelength.…”
Section: Dual-polarized Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The initial part of the numerical simulation is to engineer the geometric structure of the sensor, after structural engineering is carried out, work continues to define the constituent materials of each designed geometric structure, such as defining the RI of air holes, defining RI of SiO2 material using (6), and the last is to define plasmonic material (gold). After the design and material have been defined in COMSOL multiphysics, a mode analysis of the design is performed with the ultimate gold of obtaining the imaginary effective RI for each wavelength.…”
Section: Dual-polarized Sensitivity Analysismentioning
confidence: 99%
“…Also, several sensing techniques have been reported by many researchers, including the Mach Zehnder interferometer technique. Optical-based recently, the combination of SPR-PCF has given rise to technologies, the component is widely used in many fields, such as temperature sensors, refractive index (RI), strain, magnetic field (MF), and biological samples [6]. Not only that, various studies have reported, this component can measure more than one physical quantity simultaneously like measuring temperature and RI simultaneously, RI and MF simultaneously, and temperature and RI simultaneously [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology is susceptible to electromagnetic interference and has poor stability. Thereby, it is extremely urgent to develop wireless passive temperature measurement systems [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%